Modelo de Gestión de Servicio al Cliente para el Hotel Chimborazo Internacional de la Ciudad de Riobamba, Provincia de Chimborazo. - Pinduisaca Manjarrés, Pamela del Rocío (2012)
This work will provide a right answer to the necessities existing in the Chimborazo International Hotel in the administrative and management area to improve the service that is offered to the customer and obtain satisfaction, as well as to improve the labor level of the employee who are the people directly related with the service. For the investigation, an internal study in the enterprise was carried out through a problem tree and a SOWT (FODA) analysis which determined that the hotel has a non qualified staff that perform many functions, there is a bad planning, lack of knowledge about the vision, mission and objectives, absence of staff selection process, there are not instructions to the customer service, this produces a loss of prestige of the enterprise. After this, a survey was applied to internal and external customers, it helped us to detect that 81% of the staff says that there is no real attention to human resources, 69% do not have clear functions, 81% argues that there is not a process of personal selection, 75% think there is not a good working atmosphere and 75% do not have instructions for the customer. In relation to external clients, 52% are unsatisfied with the service, 71% believe that the hotel does not have a defined planning, according to 64% of people, the service given does not fit the customers’ needs, 80% think that the staff is not qualified, 88% noted that staff performs multiple functions. With this information it was possible to make a model of customer service management, which details the minimum requirements that the hotel must have, the enterprise internal structure was set (mission, vision, objectives, policies, goals), the functions of the employees were determined, the staff selection and contracting processes were defined, an internal regulation of the hotel was carried out, it is for employees and guests, the customer service was specified according to standards. As a conclusion it can be said that managing the hotel based on management helps controlling the activities and the advantage of the resources, the integration of the staff in the efficient development of the enterprise and the good service for the complete satisfaction of the customers.